Tata Kelola Keuangan Gereja: Panduan Penyajian Laporan Keuangan Untuk Entitas NonLaba - Paru, Sara Marlyn; Bleskadit, Novalia Herlina; Pangayow, Bill J.C; Falah, Syaikhul; Rofingatun, Siti; Siahay, Adolf ZD; Salle, Hesty T.; Prasetyo Arjuna, Bucek Jalu (The Community Engagement Journal, 2025)
The church is a non-profit organization that is not oriented to seek profit but generates income which is then managed to run programs or finance church operations. The GKI Synod is the oldest Protestant organization in Papua that has a mission to spread the gospel not only to reach urban areas but also remote areas. On February 18, 1994, the GKI Synod released a technical guideline for managing church treasury which includes financial records, budgeting, financial administration, and inventory. The GKI church financial management system is called Dirham which then becomes a standard guideline for compiling church financial reports and must be used by all GKI churches in Papua. The use of Dirham as a financial recording system recognized by the GKI church cannot be fully implemented by the church treasurer. Lack of knowledge and experience is an obstacle in presenting financial reports. For this reason, this community service activity focuses on improving the understanding of basic accounting and financial transaction recording practices, using ISAK 35 as a guideline for financial accounting standards that are generally applicable in Indonesia. Implementation of community service activities at the GKI Salem Church, Kemtuk Gresi District, Jayapura Regency. The treasurer and pastor of the congregation admitted that the lack of knowledge and experience was one of the factors that hampered the process of presenting financial reports. In the future, the GKI Synod through the Classis needs to consider aspects that hinder the governance of financial presentation, namely by implementing routine financial training and socializing GKI regulations on treasury and church financial supervision. Keywords: non-profit accounting, protestant church, ISAK 35